If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = x * 2 + x Reorder the terms for easier multiplication: 9 = 2x + x Combine like terms: 2x + x = 3x 9 = 3x Solving 9 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 9 + -3x = 0 Add '-9' to each side of the equation. 9 + -9 + -3x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 0 + -9 -3x = 0 + -9 Combine like terms: 0 + -9 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| -6a+7a=-16+3a | | y/10+4=16 | | n/-5=15 | | 36=(x+4)*2+x*2 | | -7x^2+2x+2=0 | | (-2/3)3 | | T-6=16 | | 9(x+8)-12=8(x+8)-10 | | 4x+2x-5/3=2x-7 | | 8m-13=13-8n | | -6+w=-28 | | -3.5+2x=-13.5 | | 13x-(5x-11)=13 | | n/7.2+4.5=6.4 | | x+.0805x=924 | | x/-2=5.8 | | 3(5x+7)-2(5x-4)= | | x^2-8kx=14 | | c/4=101/2 | | t/0.5=26 | | n/10=-361/5 | | 15=h-7 | | 8[3+8(36)]= | | b+19=48 | | 16x=320 | | a/-0.7=-8 | | 72=6n | | h/-1=-4.7 | | 2-3t=-1/3(5-t)+1 | | e/-1=12.5 | | 10(0.1d-0.3)=0.2(d+21) | | d/20=-1/5 |